2014
DOI: 10.1158/1055-9965.epi-13-0574
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of Adiponectin Multimers in Healthy Men Undergoing Screening for Prostate Cancer

Abstract: BACKGROUND Adiponectin has been reported to have a prohibitory effect on prostate cancer. The goal of this study was to evaluate the diagnostic value of adiponectin multimers for prostate cancer. METHODS Total adiponectin, high- and low molecular weight (HMW, LMW), ratios of these measures, and body mass index (BMI) were compared in a prospective prostate cancer screened cohort. Multivariable logistic regression was used to assess the association between adiponectin measures, their interaction with BMI, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
12
0
Order By: Relevance
“… 9–13 However, not all epidemiologic studies support this inverse association of APN and PCA. 14–16 In the present study, our extensive analysis of the association between serum APN, PSA, and CDR among 2,939 men who attended a PCA screening revealed several interesting findings.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“… 9–13 However, not all epidemiologic studies support this inverse association of APN and PCA. 14–16 In the present study, our extensive analysis of the association between serum APN, PSA, and CDR among 2,939 men who attended a PCA screening revealed several interesting findings.…”
Section: Discussionmentioning
confidence: 50%
“…A considerable number of case control studies 9–16 and cross-sectional studies 17,18 testing the association of PCA with APN have been published. In accordance with other types of cancer, most of these investigations showed an inverse association of APN levels and high-stage or high-grade PCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduced APN levels were associated with tumor stage in obese and overweight men, but not in normal weight men or overall in all men 135 . Other studies have also found no significant association between APN levels and PrC risk 136,137 . Interestingly, APN was also seen to have anti-proliferative, but not anti-apoptotic effects on human PrC cells 138 .…”
Section: Prostate Cancer (Prc)mentioning
confidence: 81%
“…Further findings indicated that endogenous adiponectin functioned as a tumor suppressor through inhibiting epithelial-to-mesenchymal transition of PCa cells [35]. On the other side, some researchers presented negative results, suggesting that adiponectin may not play an important role in promoting clinically aggressive PCa [36,37]. As mentioned before, the consumption of adipose tissues in advanced PCa, rather than tumor itself, might also cause the decrease of adiponectin.…”
Section: Discussionmentioning
confidence: 92%